2014
DOI: 10.1177/0021909614522948
|View full text |Cite
|
Sign up to set email alerts
|

Bororo Fulani Pastoralists and Yoruba Farmers’ Conflicts in the Upper Ogun River, Oyo State Nigeria, 1986–2004

Abstract: This article, based on in-depth oral interviews, focuses on the conflicts between Bororo Fulani pastoralists and Yoruba farmers in Saki and Iseyin towns of the Upper Ogun River (Oke-Ogun), Oyo State Nigeria to show the power disparity and competition over land resources. The conflicts that occurred between Bororo Fulani pastoralists and Yoruba farmers are classified as: economic (crop destruction and cattle killing); social (murder, rape, armed banditry, molestation on both sides of the conflict); and communal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…We explored relevant theories that could explain our findings from field observations and interviews. We found appealing with the concepts of moral wrongs (Turner 2004) and indigeneity (Maiangwa 2017), which can be found in many studies of the FHCs in Agogo, Ghana (Bukari & Schareika 2015;Bukari & Kuusaana 2018) and in South-West region especially Oyo State of Nigeria (Olaniyi 2015;Ogundairo & Ijimakinwa 2021) helpful in the analysis of the triggers of violence in the FHR in SEN. We found that enactment of the violence was influenced by the action of the actors perceived to be morally wrong, which then caused heightened emphasis on indigeneity leading to practices of exclu-sion and discrimination in resources. A closer look at this mechanism shows the relevance of the political ecology approach to the analysis of FHCs.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…We explored relevant theories that could explain our findings from field observations and interviews. We found appealing with the concepts of moral wrongs (Turner 2004) and indigeneity (Maiangwa 2017), which can be found in many studies of the FHCs in Agogo, Ghana (Bukari & Schareika 2015;Bukari & Kuusaana 2018) and in South-West region especially Oyo State of Nigeria (Olaniyi 2015;Ogundairo & Ijimakinwa 2021) helpful in the analysis of the triggers of violence in the FHR in SEN. We found that enactment of the violence was influenced by the action of the actors perceived to be morally wrong, which then caused heightened emphasis on indigeneity leading to practices of exclu-sion and discrimination in resources. A closer look at this mechanism shows the relevance of the political ecology approach to the analysis of FHCs.…”
Section: Introductionmentioning
confidence: 86%
“…The environmental scarcity and climate change framing has dominated the discussion of the FHCs in Nigeria until recently. Other possible explanations are emerging, including the idea of how identity differentials interact with environmental and ecology factors (Olaniyi 2015;Ogundairo & Ijimakinwa 2021). This paper seeks to contribute to this aspect of the FHCs from the standpoint of political ecology within the broader Human Geography sub-discipline.…”
Section: The Political Ecology Of the Farmer-herder Conflictsmentioning
confidence: 99%
“…10 In fact, the farmerherder conflict has evolved into armed banditry involving cattle rustling, destruction or theft of farm crops, kidnaping, and armed robbery. As noted in Olaniyi (2015), unlike the sedentary Fulani, the Bororo Fulani herders are considered very aggressive and always fully armed with AK-47 s, charms, and cutlasses and attack farmers and communities with lethal weapons.…”
Section: Background: Conflict In Nigeriamentioning
confidence: 99%
“…In fact the farmer herder conflict has evolved into armed banditry involving cattle rustling, destruction or theft of farm crops, kidnapping and armed robbery. As noted in Olaniyi(2015), unlike the sedentary Fulani, the Bororo Fulani herders are considered very aggressive and always fully armed with AK-47s, charms, cutlasses and attack farmers and communities with lethal weapons.…”
Section: Background: Conflict In Nigeriamentioning
confidence: 99%